Aromatherapy candle formulation from Citrus microcarpa peel - Meryta; Husnayanti, Ana; Sinulingga, Syamsul Rizal; Sudirman, Muhammad Seto (Pharmacy Reports, 2022)
Candles can serve a dual purpose of not only providing light but also acting as a means of aromatherapy. Aromatherapy, which involves the use of essential oils, such as calamansi peel (Citrus x microcarpa Bunge), is an alternative form of treatment. The objective of this study was to determine the optimal concentration of essential oil, evaluate the characteristics of aromatherapy candles, and assess their appeal. The pre-experimental technique employed a one-time case study/post-test design, with soy wax used as the candle's wax base. The preference test for aromatherapy candles involved 30 untrained individuals. The candles exhibited a uniform color, with no cracks, defects, fractures, or air bubbles. The candle with a 3% formulation demonstrated the longest burning time and quickest melting point. Furthermore, candles containing 3% essential oil were preferred both before and during burning. Additionally, this formulation displayed the fragrance promptly, with the quickest perceived effect time.